Corticostriatal Hypermetabolism in Moyamoya Disease-Induced Hemichorea: Two Case Reports and a Literature Review - Xian, Wen-biao; Zhang, Xiang-song; Shi, Xin-chong; Luo, Gan-hua; Yi, Chang; Pei, Zhong (Frontiers in Neurology, 2021)
Moyamoya disease (MMD) is a rare cause of chorea, and its pathophysiological mechanism remains unclear. We explore the use of cerebral positron emission tomography (PET) to study brain functional connectivity in 2 patients with MMD-induced hemichorea. Abnormal metabolism of brain was analyzed by 18F-fluorodeoxyglucose (18F-FDG) PET images. Dopamine transporters (DAT) PET evaluated the integrity of the cerebral dopamine system. A comprehensive systemic literature search of the PubMed database was also conducted. The 18F-FDG imaging of our patients showed no responsible hypometabolism in affected brain areas, while hypermetabolism in the affected caudate nucleus, putamen and fronto-parietal areas could be seen. DAT PET imaging was normal in patient 1 (a 23-year-old woman), while remarkably reduced DAT binding was seen in the left striatum of patient 2 (a 48-year-old woman). The literature review of 9 publications revealed that 11 patients who underwent single photon emission computed tomography (SPECT) showed cerebral hypoperfusion in the cortex and subcortical area; 18F-FDG PET was performed in 3 cases, which revealed hypermetabolism in the affected striatum in 2 cases. These findings suggest that the striatal and cortical hypermetabolism in the our first patients result from underactivity in indirect pathway from basal ganglia-thalamocortical circuits, causing increased activity of excitatory glutamatergic thalamostriatal and thalamocortical projection neurons. The collateral vessels in the basal ganglia or striatal hypoperfusion might lead to disruption of normal basal ganglia signaling. A dominant left hemisphere with corpus callosal connections to the right basal ganglia resulting into left hemichorea is the most probable explanation for the second patient. We have identified abnormal functional connectivity in basal ganglia-thalamocortical circuits in patients with MMD-induced chorea highlighting the corticostriatal pathwaystriatal indirect pathway plays an important role in the pathogenesis of MMD-induced chorea.